The Recovery of an Undue Payment by a Manumitted Slave in Ancient Rome: A Reading of Digest 12.4.3.7 in Light of the Theory of Social Acts according to Adolf Reinach - El Beheiri, Nadja (Strathmore Law Journal, 2022)
In his comment on the Pretorian edict the ancient Roman jurist Ulpian (+228) refers to a case where positive law (ius civile) and natural justice (aequitas naturalis) came into collision. A slave was manumitted in a will under the condition of paying 10 to the heir. Subsequently the owner of the slave made a second informal will (codicillus) where he manumitted the slave without mentioning any condition. After his masters dead the slave being ignorant of the second will paid 10. The question arose whether he could recover the money. The case was decided first by the elder Celsus who hold that the slave could not recover the money. On the contrary, the younger Celsus stated that the recovery of the money was possible. This latter jurist made his decision – as Ulpian stated – influenced by a feeling of natural justice. In the present paper we analyse the case will be also analysed from the perspective of theory of social acts developed by Adolf Reinach, one of the most outstanding members of the realistic branch of phenomenological school. Furthermore, a relationship is established between the present case and the Rescript of the Emperor Hadrian according to which a demand for operae could not be reinforced in case that the patronus was obliged to free the slave through a fideicommissum.